2015
DOI: 10.1155/2015/714963
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Complete Denture in Patients with Ectodermal Dysplasia

Abstract: Ectodermal dysplasia is described as heritable conditions that involve anomalies of structures derived from the ectoderm, including hypodontia. In the cases of edentulous young patients, who did not finish their craniofacial growth, treatment with conventional complete denture is a suitable alternative. The aim of this study was to report a case of mandibular edentulism treated with conventional complete denture in a thirteen-year-old patient diagnosed with hidrotic ectodermal dysplasia. Typical features, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
0
4
0
6
Order By: Relevance
“…42 Not all cases are suitable for a BPS denture even though they have better stability and retention ie; better suction effect,conventional cd is preferred which can also show good results . 43 When we consider rehabilitation in a complete denture patient to achieve a pleasant smile aesthetics plays a vital role. 44,45 Future scope is a prospective study of the denture and the patient satisfactory level on a long term basis can be evaluated and can make use of Electromyography for a much precise value of the muscle activity with a review both pre op and post operative of denture placement review each month.…”
Section: Resultsmentioning
confidence: 99%
“…42 Not all cases are suitable for a BPS denture even though they have better stability and retention ie; better suction effect,conventional cd is preferred which can also show good results . 43 When we consider rehabilitation in a complete denture patient to achieve a pleasant smile aesthetics plays a vital role. 44,45 Future scope is a prospective study of the denture and the patient satisfactory level on a long term basis can be evaluated and can make use of Electromyography for a much precise value of the muscle activity with a review both pre op and post operative of denture placement review each month.…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31] A removable dental prosthesis remains more feasible alternative compared to fixed teeth-supported or implant-supported prostheses because the removable prosthesis is less invasive, more affordable, and it is easier to maintain oral hygiene. [38] Swelem et al, [21] reported on patient satisfaction, and quality of life assessment among removable dental prosthesis wearers suggested that comfort, general satisfaction, and masticatory efficiency were significantly higher after conventional treatment and continued to improve significantly after the use of attachments. The use of such attachments increases prosthesis retention and stability in an aesthetically more pleasing way and may improve the patient's acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Dessa forma, a utilização de próteses removíveis é a escolha padrão ouro para pacientes pediátricos, pois são alternativas interessantes e práticas que fornecem uma solução relativamente rápida, fácil, agradável e econômica para reabilitação oral estética e promove benefícios psicológicos em pacientes jovens, com edentulismo pronunciado (TARJAN I, GABRIS K, ROZSA N, 2005;MAROULAKOS G, et al, 2016;VILANOVA LSR, et al, 2015). Essa solução melhora a qualidade de vida do paciente e otimiza a integração social, e além disso, a instalação de prótese em idade precoce tem a vantagem de melhorias significativas nas funções da fala e mastigação (MAROULAKOS G, et al, 2016).…”
Section: Discussionunclassified